PENGARUH ENDORSER SELEBRITI DAN GAYA HIDUP HALAL TERHADAP MINAT BELI SKINCARE GENERASI Z DI JAWA TIMUR - Jannah, Wildatul; Rahma, Siti Habibatur (Universitas Airlangga, 2025)
Indonesia's potential in the halal skincare industry is significant, as evident from its position as the second largest consumer of halal cosmetics and the high enthusiasm of Generation Z towards self-care products. Generation Z's increasing interest in skincare has driven a significant expansion of Indonesia's beauty industry. This generation is known for being active on social media and has a high awareness of appearance and personal values, including a halal lifestyle. This research aims to analyze how celebrity endorsers and the halal lifestyle influence Generation Z's purchase interest in skincare in East Java. The study uses a quantitative approach. The participants are Generation Z skincare users. The sample was chosen through a non-probability purposive sampling method, with specific criteria, involving 110 respondents who reside in East Java and were born between 1995 and 2012. Data was collected via an online survey and analyzed using IBM SPSS Statistics 31. This research includes tests such as instrument validation, classical assumption tests, hypothesis testing, and regression analysis. The results show that, partially, celebrity endorsers and the halal lifestyle significantly affect purchase interest. Together, both factors, celebrity endorser and the halal lifestyle, also significantly influence Generation Z's skincare purchase interest in East Java. This result helps create more successful marketing tactics, particularly the utilisation of public figures and the strengthening of halal product images. Skincare companies are advised to choose celebrity endorsers who are popular and trustworthy and align with halal lifestyle values